Excitation Mechanisms and Characterization of a Multi-Ionic Xenon Laser - Sobral, Hugo Martín (1999)
The emission characteristics of an ultraviolet-visible pulsed multi-ionic xenon laser were studied through time-resolved spectroscopy and the results were interpreted using a collisional radiative theoretical model. This analysis includes more than 20 laser lines belonging to several ionic species (Xe III VIII). Depending on the experimental conditions, different temporal distributions of the laser lines and their corresponding sponta neous emissions can be observed. In particular, laser emission presents temporal oscillations near threshold. Pumping processes for the laser transitions have been analyzed by using this model. Relativistic Hartree Fock calculations of laser level lifetimes and radiative transition probabilities were performed. Experimental laser gain for several transitions were obtained and compared with the theoretical values derived from the calculations.